Crop Improvement New Approaches and Modern Techniques - Hakeem, Khalid Rehman; Ahmad, Parvaiz; Ozturk, Munir (Springer US : Imprint: Springer, 2013)
The improvement of crop species has been a basic pursuit since cultivation began thousands of years ago. To feed an ever increasing world population will require a great increase in food production.  Wheat, corn, rice, potato and few others are expected to lead as the most important crops in the world.  Enormous efforts are made all over the world to document as well as use these resources. Everybody knows that the introgression of genes in wheat provided the foundation for the "Green Revolution". Several factors are contributing to high plant performance under different environmental conditions, therefore an effective and complementary use of all available technological tools and resources is needed to meet the challenge.   New Approaches and Modern Techniques highlights the current status of crop productivity in the light of  developments in crop biotechnology, and at the same time  provides information on some recent genomic tools and novel genetic and breeding approaches with a final aim of crop improvement. Emphasis has been laid on the topics related to advances in crop biotechnology, the key principles influencing the current practice in crop improvement programs and elucidate the nature of new approaches as well as modern techniques in crop improvement and how molecular plant breeding opens new avenues for research and is contributing to discoveries in this field. .